Urdu ka guldasta - Genda : for class 2 . - Fozia Ahsaan Farooqi (Karachi ; Oxford university press, 2021)
Urdu ka guldasta Genda is a prominent collection that celebrates the richness of Urdu poetry and prose. It features a variety of literary works from renowned poets and writers, showcasing the intricate beauty and emotional depth of the Urdu language. The book is designed to appeal to both seasoned literature lovers and newcomers, offering a diverse range of themes and styles. Through its carefully curated selections, it not only highlights the artistic expression found in Urdu literature but also emphasizes its cultural significance, making it a valuable addition to any literary collection.
Keywords: Urdu - text book; Urdu - grammar; Urdu - literature